A bridge between quaternionic and complex numerical ranges - Carvalho, L.; Diogo, C.; Mendes, S. (Linear Algebra and its Applications, 2019)
We obtain a sufficient condition for the convexity of quaternionic numerical range for complex matrices in terms of its complex numerical range. It is also shown that the Bild coincides with complex numerical range for real matrices. From this result we derive that all real matrices have convex quaternionic numerical range. As an example we fully characterize the quaternionic numerical range of 2 x 2 real matrices.